Free radical graft copolymerization of N-vinyl-2-pyrrolidone onto k-carrageenan in aqueous media and applications - Mishra, Madan Mohan; Sand, Arpit; Mishra, Dinesh Kumar; Yadav, Mithilesh; Behari, Kunj (Carbohydrate Polymers, 2010)
In the present article, the graft copolymer of k-carrageenan with N-vinyl-2-pyrrolidone (NVP) has been synthesized using PMS/maleic acid as a redox initiator in aqueous medium and reaction conditions have been optimized to obtain maximum % grafting ratio (%G). The optimum conditions of maximum grafting have been found by varying the different parameters. On increasing the concentration of maleic acid and peroxymonosulphate from 1.6 x 10(-3) to 4.8 x 10(-3) mol dm(-3) and 0.6 x 10(-2) to 2.2 x 10(-2) mol dm(-3) respectively, the initially grafting parameters increased and after a certain range of concentration grafting parameters showed decreasing trend. The small increment of concentration in hydrogen ion causes increment in percentage grafting. It was observed that the grafting parameters increase as the concentration of N-vinyl-2-pyrrolidone increases up to 16 x 10(-2) mol dm(-3) after that it decreased. The optimum condition for maximum grafting has obtained at concentration 1.0 g dm(-3) of k-carrageenan at 40 degrees C and 120 min, respectively. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: flocculation; Graft copolymer; k-Carrageenan; Metal ion uptake; N-vinyl-2-pyrrolidone; swelling

Alginic acid-g-poly(N-vinylformamide) graft copolymer: synthesis, characerization, swelling, and flocculation property - Sand, Arpit; Yadav, Mithilesh; Mishra, Dinesh Kumar; Behari, Kunj (Journal of Applied Polymer Science, 2011)
The graft copolymer of N-vinylformamide with alginic acid was synthesized by free radical polymerization using potassium peroxymonosulphate and thiourea as redox pair in inert atmosphere. The optimum conditions for maximum grafting have been determined by varying the concentrations of N-vinylformamide, potassium peroxymonosulphate, thiourea, sulfuric acid, alginic acid as well as time duration and temperature. The grafting parameters increase up to the certain concentrations of N-vinylformamide, potassium peroxymonosulhate, thiourea, and hydrogen ion while thereafter grafting parameters decrease. The effect of alginic acid concentration on grafting parameters has been observed to decrease continuously. It has also been found that grafting parameters increase up to certain time and temperature, respectively, and thereafter decrease. The swelling properties of graft copolymer in terms of swelling ratio and percent swelling are investigated. Flocculation property of pure and grafted sample for both coking and noncoking coals is also investigated for the treatment of coal mine waste water. The graft copolymer has been characterized by Fourier transform infrared spectroscopy as well as thermogravimetic analysis. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 1400-1407, 2011
Keywords: alginic acid; flocculation; Graft copolymer; N-vinylformamide; swelling